EFFECT OF LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE IN CLASS II OFFICIAL OFFICES OF REZA BERAWI KOTA BANDAR LAMPUNG - Aprianis .; Dharmawan . (Saburai International Journal of Social Sciences and Development, 2020)
This study aims to see the influence of leadership and organizational culture on the performance of employees at Reza Berawi Class II Auction Officers in Bandar Lampung City. The type of research used in this study is an explanatory research model. The research method used is quantitative. This study used 20 research respondents. There are three variables in this study, namely: 2 independent variables (X1 and X2) and 1 (one) leadership relationship variable (X1) and organizational culture (X2) as independent variables and employee performance (Y) as the dependent variable.Based on the results of data processing, the hypothesis answers are found as follows; there is a leadership influence (X1) on employee performance (Y), with a level of influence (R2) of 44.6%. There is an influence of organizational culture (X2) on employee performance (Y) with a level of influence of 33.9%. There is a joint influence of leadership (X1) and organizational culture (X2) on employee performance (Y), with a level of influence of 53.3%.